Understanding Customer Loyalty Through Technology Acceptance and Customer Experience: The Mediating Role of Customer Satisfaction in Multichannel Vegetable Retail - Rejeki, Septiadinur; Setiawan, Budi; Isaskar, Riyanti (HABITAT, 2026)
Purpose: The rapid development of the retail sector driven by digital technology and accelerated by the COVID-19 pandemic has transformed consumer shopping behavior and intensified competition in the retail industry. Retailers are increasingly adopting multichannel marketing strategies by integrating physical and digital channels to meet changing consumer preferences. However, limited studies have examined the role of technology acceptance in shaping customer experience, satisfaction, and loyalty simultaneously within a multichannel context, particularly in vegetable retail businesses. Therefore, this study aims to analyze the influence of technology acceptance on customer experience, satisfaction, and loyalty. Design/Methodology/Approach: This research uses quantitative research methods. The criteria respondents are women have online and offline shopping experience. The data analysis method uses Structural Equation Model (SEM)-PLS with WarpPLS7.0. Findings: The result is acceptance of technology has positive and significant effect on experience, satisfaction and loyalty. However, technology acceptance does not have a positive and insignificant effect on loyalty. Experience has a positive and significant effect on satisfaction and loyalty. Satisfaction has a positive and significant effect on loyalty. Customer experience has a positive and significant effect on loyalty through satisfaction. Originality/Value/Novelty: This study provides new insights by integrating technology acceptance, customer experience, satisfaction, and loyalty within a multichannel vegetable retail context. The findings highlight the importance of technology-supported customer experiences in enhancing satisfaction and fostering customer loyalty in multichannel retail environments.